2021
DOI: 10.1210/clinem/dgab601
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Glucose Monitoring in the Management of Neonates With Persistent Hypoglycemia and Congenital Hyperinsulinism

Abstract: Background Persistent hypoglycaemia is common in the newborn and is associated with poor neurodevelopmental outcome. Adequate monitoring is critical in prevention, but is dependent on frequent, often hourly blood sampling. Continuous glucose monitoring (CGM) is increasingly being used in children with type 1 diabetes mellitus, but use in neonatology remains limited. We aimed to introduce real-time CGM to provide insights into patterns of dysglycaemia and to support the management of persisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 25 publications
2
20
0
Order By: Relevance
“…-not possible to compute, NA, not applicable. errors (12) by graphical methods that categorised errors into discrete grids (13). However, existing error grids do not accurately represent the risk of CGM inaccuracy for patients with CHI as they are designed to test accuracy in patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…-not possible to compute, NA, not applicable. errors (12) by graphical methods that categorised errors into discrete grids (13). However, existing error grids do not accurately represent the risk of CGM inaccuracy for patients with CHI as they are designed to test accuracy in patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The first report for the Dexcom system (G5) came in 2019 with 1155 paired values giving a MARD of 17.5%, a mean difference of -1.01 mmol/L (-8.09mg/dL) and no error grid analysis ( 12 ). Two more recent studies from mixed populations including some patients with CHI (60-64%) have shown MARD of 11.0% ( 13 ) and 13.1% ( 14 ) with one study plotting paired values on a CEG. These analyses all include multiple values of glucose >4mmol/L which are of great importance to a patient living with diabetes who may have to adjust insulin doses at higher glucose ranges but of limited practical interest to most patients with CHI who use CGM exclusively for hypoglycaemia detection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CGM is used in children with type 1 diabetes mellitus, but less so in neonatology. A single-center retrospective study reported the use of real-time CGM over a 4-year period in neonates with hypoglycemia [ 43 ]. Although CGM has been shown to reduce morbidity in type 1 diabetes pregnancy LGA offsprings, a recent large multicenter observational cohort study on CGM with 300 pregnant women with type 1 diabetes found that neonates were more likely to be hypoglycemic [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is growing interest in the application of CGM to improve glycaemic control in neonates with CHI (12,13). Win et al reported that CGM showed rapid fluctuations in glucose levels in fourteen neonates with CHI alongside persistent hypoglycaemia, reflecting the high risk of undetected hypoglycaemic episodes when managed on intermittent fingerprick glucose tests (14). Rayannavar et al's observational study demonstrated a high false positive rate for hypoglycaemia readings for children with CHI over a two-week period; the authors determined that CGM should be used as an adjunct to glucose monitoring rather than a sole monitoring device due to its suboptimal accuracy (15).…”
Section: Introductionmentioning
confidence: 99%